2016
DOI: 10.1002/ejic.201601025
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Crystal Growth of a {V14Sb8O42} Cluster from a {V15Sb6O42} Polyoxovanadate: In Situ XRD Studies

Abstract: The hydrothermal transformation of the heteroatom polyoxovanadate compound {Ni(en)3}3[V15Sb6O42(H2O)]·≈15H2O (en = ethylenediamine) in water into [{Ni(en)2}2V14Sb8O42]·5.5H2O was investigated by in situ XRD experiments at different temperatures. First, the precursor undergoes very fast amorphization or dissolution, and an induction period is observed that depends on the reaction temperature. Crystal growth of the product is completed within 3 h, while higher temperatures lead to accelerated reaction progress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…[10][11][12][13][14][15][16][17][18][19][20] Also, severalS b-POVs exist that feature clusteranionsexpanded by transition-metal complexes, as exemplified by [V 16 [10,11,23,24] With increasingr eaction temperature and time, formation of the Sbricherc lustera nion is favored. [24] During our investigations of zinc-containing antimonato polyoxovanadates in hydrothermala queous en solutions, we discoveredt he new compound {Zn(en) 3 [24] During our investigations of zinc-containing antimonato polyoxovanadates in hydrothermala queous en solutions, we discoveredt he new compound {Zn(en) 3 …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20] Also, severalS b-POVs exist that feature clusteranionsexpanded by transition-metal complexes, as exemplified by [V 16 [10,11,23,24] With increasingr eaction temperature and time, formation of the Sbricherc lustera nion is favored. [24] During our investigations of zinc-containing antimonato polyoxovanadates in hydrothermala queous en solutions, we discoveredt he new compound {Zn(en) 3 [24] During our investigations of zinc-containing antimonato polyoxovanadates in hydrothermala queous en solutions, we discoveredt he new compound {Zn(en) 3 …”
Section: Introductionmentioning
confidence: 99%
“…N undergoes one or two one-electron oxidations of V IV to V V during the ionization process,y ielding doubly and triply charged ions in case of the cluster ions without chargecompensating cations.W enote that the mass spectrum of 2 is quite similar to that of its well-studied precursor 1 [4] (see Figure S18 for ad etailed isotope pattern analysis 3À at m/z 1304 and 1738, respectively. Thed imer ions are seen over aw ide range of sample concentrations indicating that dimer formation is not merely unspecific aggregation during the ESI process.F urthermore,acontrol experiment with the a-{V 14 Sb 8 O 42 } [17] Thep eak of the tetraanionic dimer complex overlaps with the peak of the doubly charged monomeric complex at the same m/z,b ut can be separated via traveling-wave ion-mobility mass spectrometry ( Figure S19).…”
mentioning
confidence: 99%
“…The ESI‐MS investigations indicated that the {V 15 Sb 6 O 42 }→{V 14 Sb 8 O 42 } transformation could be accelerated by the addition of ammonium additives . Under stirring conditions, the transformation could reach full conversion after only 4 h at 150 °C, resulting in formation of [{Ni(en) 2 } 2 V 14 Sb 8 O 42 ]⋅5.5H 2 O featuring the β ‐isomer of the {V 14 Sb 8 O 42 } moiety . This fast reaction progress allowed investigation of the conversion by in situ‐XRD experiments at the DESY (German Electron Synchotron) facility in Hamburg.…”
Section: Reactivity Of Sb‐povsmentioning
confidence: 97%
“…The insights gained when studying the reactivity of the {V 15 Sb 6 O 42 } cluster in compound 10 have proven to be highly valuable for the further development of Sb‐POV chemistry. The versatility of this high‐nuclearity precursor was demonstrated in a number of post‐functionalization reactions, thereby broadening the field of new Sb‐POVs (Scheme ) . The use of this new precursor has enabled the increase in structural complexity of the obtained cluster products, which have partially undergone the {V 15 Sb 6 O 42 }→{V 14 Sb 8 O 42 } transformation after short reaction times.…”
Section: Reactivity Of Sb‐povsmentioning
confidence: 99%